Complete percutaneous myocardial revascularization in patients with STEMI complicated by cardiogenic shock - Petrović Milovan; Jaraković Milana; Čanković Milenko; Srdanović Ilija; Kovačević Mila; Tešić Dragica; Ivanović Vladimir; Redžek Aleksandar; Velicki Lazar (Vojnosanitetski Pregled, 2019)
Background/Aim. Despite considerable progress in terms of early myocardial revascularization and the use of mechanical circulatory support, cardiogenic shock continues to be the leading cause of death in acute myocardial infarction. The current recommendations of the European Society of Cardiology advocate early revascularization of all critical stenosis or highly unstable lesions in the state of cardiogenic shock, while recently published studies favour the early revascularization of the infarct related artery only, in patients with acute myocardial infarction with the ST segment elevation (STEMI) presenting with cardiogenic shock. The aim of the study was to assess the impact of the complete early percutaneous myocardial revascularization in an acute myocardial infarction complicated by cardiogenic shock on intra- hospital mortality. Methods. The research was conducted as a retrospective observational analysis of data obtained from the hospital registry for cardiogenic shock. The study group consisted of 235 patients treated in the period from August 2007 until October 2016 for STEMI complicated by cardiogenic shock. Three groups were formed. The first group consisted of patients with one vessel disease who underwent revascularization of infarct related artery; the second group of patients had multi-vessel disease and only culprit lesions were revascularized and the third one consisted of patients with multi-vessel disease and the complete myocardial revascularization performed. Additional subgroups were formed in reference to the intra-aortic balloon pump (IABP) implantation. Intra-hospital mortality was analyzed in all groups and subgroups. Results. Revascularization of the culprit lesion alone among patients with multivessel disease was performed in 142 (60.4%) patients while the complete revascularization (revascularization of “culprit” and other significant lesions) was performed in 28 (11.9%) patients with multi-vessel disease. There were 65 (27.7%) patients with single-vessel disease who underwent revascularization of infarct related artery. The lowest mortality was found in the group of patients with multi-vessel coronary disease who underwent complete myocardial revascularization and had IABP implanted (mortality was 35.7%). The difference in the mean value of the left ventricular ejection fraction (EF) between the surviving and deceased patients was statistically significant (p < 0.005). The average EF of survivors was 44% (35%–50%) while 30% (25%–39.5%) deceased of patients. Based on the obtained data, the mathematically predictive model was tested. The receiver operating characteristic (ROC) curve showed that our model is a good predictor of fatal outcome (p < 0.0005; AUROC = 0.766) with the sensitivity of 80.3%, and the specificity of 67%. Conclusion. STEMI complicated by cardiogenic shock is still associated with a high mortality rate. Complete myocardial revascularization independently as well as in combination with an IABP, significantly reduces mortality in patients with acute STEMI complicated by cardiogenic shock.